Griefing and Deception in Video Games: Examining Attitudes towards the Phenomena - Rubin, Victoria L.; Camm, Sarah C. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Though not new to online gamers, griefing – an act of play intended to cause grief to game players – is understudied in LIS scholarship. We expand on the definition of griefing for library contexts by considering its deceptive elements and examining gamers’ attitudes in a gaming forum and an e-mail survey. Bien que connu des joueurs de jeux vidéo, le terme griefing, qui fait référence à un acte dont le but est de gêner ou d’emmerder les autres joueurs, est sous-étudié dans le domaine de la bibliothéconomie et des sciences de l’information. Nous avons étendu la définition de griefing au contexte bibliothéconomique en considérant sa nature trompeuse et en examinant les attitudes des joueurs d’un forum de jeu et les réponses d’un questionnaire par courriel.